The design, construction, operation and performance of the Belle II silicon vertex detector. (1st November 2022) - Adamczyk, K.; Aggarwal, L.; Aihara, H.; Aziz, T.; Babu, V.; Bacher, S.; Bahinipati, S.; Bari, M.; Baroncelli, Ti.; Baroncelli, To.; Bassi, G.; Batignani, G.; et al.
Abstract: The Silicon Vertex Detector of Belle II is a state-of-the-art tracking and vertexing system based on double-sided silicon strip sensors, designed and fabricated by a large international collaboration in the period 2012–2018. Since 2019 it has been in operation providing high quality data with a small number of defective channels (<1%), a large hit-finding efficiency (>99%), a good signal-to-noise ratio (well in excess of 10 for all sensor configurations and tracks). Together with the good control over the alignment, these are all essential factors to achieve good tracking reconstruction and physics performance. In this extended paper we try to document all the aspects of the SVD challenges and achievements, in the spirit of providing information to the broader community and help the development of high quality detector systems, which are essential tools to carry out physics research.